The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1063/1.126366
|View full text |Cite
|
Sign up to set email alerts
|

SrRuO 3 /(Ba, Sr)TiO 3 /SrRuO 3 capacitor annealed in the forming gas with and without oxygen addition

Abstract: Forming gas (3%H2+97%N2) anneals result in decomposition of SrRuO3 and increase the leakage current of the SrRuO3/(Ba, Sr)TiO3/SrRuO3 capacitor. However, we show that 0.5% O2 addition to the forming gas (3%H2+0.5%O2+96.5%N2) does not cause degradation of the SrRuO3/(Ba, Sr)TiO3/SrRuO3 capacitor, and can also enhance the performance of the transistor effectively. To correctly study the effect of a forming gas anneal on the SrRuO3/(Ba, Sr)TiO3/SrRuO3 capacitor, efforts should be made to avoid the possible O2 dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 24 publications
0
10
1
1
Order By: Relevance
“…6͑c͔͒ shifts the temperature of this process to about 450°C but the amount of 12.9% of lost substance is exactly the same. During annealing SrRuO 3 decomposed completely following the reaction proposed by Lin et al 40 ͑SrRuO 3 +2H 2 → Ru+ SrO + 2H 2 O͒. The value of 14.8%, calculated for the full chemical reaction and taking into account 20% RuO 2 excess, slightly differed from the experimental value.…”
Section: -2contrasting
confidence: 43%
“…6͑c͔͒ shifts the temperature of this process to about 450°C but the amount of 12.9% of lost substance is exactly the same. During annealing SrRuO 3 decomposed completely following the reaction proposed by Lin et al 40 ͑SrRuO 3 +2H 2 → Ru+ SrO + 2H 2 O͒. The value of 14.8%, calculated for the full chemical reaction and taking into account 20% RuO 2 excess, slightly differed from the experimental value.…”
Section: -2contrasting
confidence: 43%
“…8 In those cases, adding 0.5% of oxygen to the forming gas can prevent the decomposition of SrRuO 3 that would normally occur when exposed to pure forming gas at 400°C for 1 h. Halley et al also reported that while the addition of 1%-2% O 2 to forming gas prevented decomposition even at temperatures as high as 700°C, heating in vacuum (10 Ϫ4 Torr) caused the decomposition of SrRuO 3 to occur around 600°C. 8 In those cases, adding 0.5% of oxygen to the forming gas can prevent the decomposition of SrRuO 3 that would normally occur when exposed to pure forming gas at 400°C for 1 h. Halley et al also reported that while the addition of 1%-2% O 2 to forming gas prevented decomposition even at temperatures as high as 700°C, heating in vacuum (10 Ϫ4 Torr) caused the decomposition of SrRuO 3 to occur around 600°C.…”
mentioning
confidence: 99%
“…It is interpreted as a built-up interface potential induced by the hydrogen and in turn the lowering of the Schottky barrier height [26,27]. Several consistent results and mechanisms have been published by NEC [30][31][32][33], Fujitsu [34,35], Hyundai [36,37], Argonne National Laboratory [38][39][40], etc. Meanwhile, several technical routines have been proposed to avoid such hydrogen damage in actual LSI/ULSI fabrication processes [31,32,35,36,[41][42][43].…”
Section: Introductionmentioning
confidence: 65%